Meating their needs: a needs assessment of meat processing businesses in Minnesota - VanderMey, Courtney (Kansas State University, 2022)
Livestock slaughter and meat processing operations play a key role in communities and are essential to small to medium-scale livestock producers. While agriculture and livestock processing are economically important to Minnesota, generating $112 billion every year in total economic impact, there are not enough local processors to meet the growing demand for local product. Previous studies about the status of the meat processing industry found that meat processing business owners were planning to transition out of the industry, but many had not finalized a plan to make the transition. This is a concern to the industry as these businesses’ services are relied upon by livestock producers and there are limited alternatives if a processing operation closes. The overall goal of this thesis is to enhance stakeholder knowledge of resource awareness and usage of technical assistance opportunities among meat processing businesses and further work on the lack of transition planning. The specific objective of this thesis is to help identify the resource and technical assistance needs of small slaughter and processing businesses in Minnesota as they plan for the future of their operation. Transition planning is addressed through understanding meat processing business owners’ status in terms of planning for the future transition of their business and to distinguish where processors turn to when seeking guidance through their businesses transition. This thesis coincides with the “Solving the Meat Processing Bottleneck” (2022) study. The data were obtained through the Solving the Meat Processing Bottleneck Team’s interview process. The resource needs of the current owners varied for each operation. Some processors felt strongly that they would benefit from each of the categories studied while others did not feel they would benefit from additional assistance. Financial resources such as capital and grants were deemed to have the greatest need for more information. Alternatively, when asked which of the resources a newcomer to the meat processing industry would benefit from, they believed there was value in offering all types of assistance. This alludes to the notion that meat processing business ownership is a difficult industry to enter as a new business owner. Interview data about transition planning show that many processors have not planned for the transition of their business. Many noted that they hoped a family member would be willing to take over their business, but they were many years away from retirement. The bottleneck in the meat processing industry has many facets, and by working to bolster the industry, processors can grow, and new processors can successfully enter the industry. In return, local communities’ benefit and can continue to thrive through additional economic development. This information will direct future resource development in communities and through state and federal policy. By understanding the degree of program utilization and future need there can be purposeful development of programs that fund and deliver opportunities for meat processors.
Keywords: Meat processing; Minnesota; Succession planning; Agribusiness; Bottleneck; Supply chain